2006
DOI: 10.1111/j.1525-1470.2006.00235.x
|View full text |Cite
|
Sign up to set email alerts
|

Double‐Blind, Randomized, Placebo‐Controlled Trial of the Use of Topical 10% Potassium Hydroxide Solution in the Treatment of Molluscum Contagiosum

Abstract: Molluscum contagiosum is a common viral infection of the skin that frequently affects children. Lesions take between 6 and 18 months to resolve spontaneously and are a source of great embarrassment to both caretakers and children, often affecting attendance at school and limiting social activity. Treatment options to date have been poorly tolerated by children but recent studies have suggested that potassium hydroxide may be beneficial. This double-blind, randomized, placebo-controlled study compared 10% potas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
6

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 15 publications
0
26
0
6
Order By: Relevance
“…Topical KOH has been shown to be beneficial in the treatment of MC lesions in children in several studies . Short et al conducted an RCT in 20 children 2 to 12 years of age and found that 10% KOH induced MC lesion clearance in 70% of the treatment group versus only 10% of the control arm (normal saline placebo applied) when the agents were applied twice daily until inflammatory changes appeared. KOH has also been compared with alternative treatments, including tretinoin and imiquimod (Table ).…”
Section: Potassium Hydroxidementioning
confidence: 99%
“…Topical KOH has been shown to be beneficial in the treatment of MC lesions in children in several studies . Short et al conducted an RCT in 20 children 2 to 12 years of age and found that 10% KOH induced MC lesion clearance in 70% of the treatment group versus only 10% of the control arm (normal saline placebo applied) when the agents were applied twice daily until inflammatory changes appeared. KOH has also been compared with alternative treatments, including tretinoin and imiquimod (Table ).…”
Section: Potassium Hydroxidementioning
confidence: 99%
“…7 More recently we have demonstrated the efficacy and safety profile of the use of potassium hydroxide (KOH) 5 to 10% in aqueous solution, in the treatment of molluscum contagious in immunocompetent children. [8][9][10] The solution must be applied at home by the patient or parents through the use of a swab on each lesion. The applications should be repeated daily until there are signs of erythema or local edema.…”
Section: Discussionmentioning
confidence: 99%
“…Short и соавт. опубликовали результаты первого двойного слепого плацебоконтролируемого исследова-ния по применению 10% раствора гидроксида калия, наносимого 2 раза/сут, у 20 детей в возрасте от 2 до 12 лет с диагнозом контагиозного моллюска [20]. Завер-шили исследование 19 пациентов.…”
Section: лечениеunclassified